Treatment of Wastewater by Ozone Produced in Dielectric Barrier Discharge - Rita Bhatta; Rachhya Kayastha; Deepak P. Subedi; Rajendra Joshi (Journal of Chemistry)
There is rapid diminishing of water resources in many countries due to, for example, population growth and constant reduction in fresh water supply. The sewage wastewater, industrial effluents, and municipal wastewater are directly and indiscriminately discharged into rivers and lakes and thus primarily cause water pollution in Nepal. This has increased the water crisis and also causes environmental deterioration. Therefore, the need for the development of an effective, cheap, and environmentally friendly process for the treatment of wastewater before discharging into aquatic environment has emerged. Treatment by ozone produced from dielectric barrier discharge is one of the emerging technologies for such application. The ozonation process is more effective for disinfection and degradation of organic pollutants from water. The current study describes the treatment of wastewater of selected site within Kathmandu. Results on various physicochemical and microbial parameters of the inlet and outlet samples are discussed. Our results showed slight increase in pH, decrease in chemical oxygen demand, and significant increase in dissolved oxygen after ozonation. Importantly, ozonation caused total reduction of fecal coliform.